(untitled) (Research, Society and Development, 2022)
Subjective happiness is a multidimensional construct that indexes assessments of emotional experiences. This article aims to describe the levels of subjective happiness of Dentistry and Psychology students. Descriptive article, regarding the field objectives, with a quantitative approach, the investigation adopted the precepts of field research, with a cross-section with direct observation and of the extensive type carried out using a questionnaire, non-probabilistic sampling. Data collection was carried out using the Subjective Happiness Scale with a link sent through WhatsApp, a procedure for dissemination and chain sampling known as snowball was adopted. The data obtained were analyzed using the Statistical Package for Social Science (SPSS 21). No significant differences were found between the participants.